(Trade) war and peace: How to impose international trade sanctions - Gustavo De Souza; Naiyuan Hu; Haishi Li; Yuan Mei (Federal Reserve Bank of Chicago, 2022)
Trade sanctions are a common instrument of diplomatic retaliation. To guide current and future policy, we ask: What is the most cost-efficient way to impose trade sanctions against Russia? To answer this question, we build a quantitative model of international trade with input-output connections. Sanctioning countries simultaneously choose import tariffs to maximize their income and to minimize Russia's income, with different weights placed on these objectives. We find, first, that for countries with a small willingness to pay for sanctions against Russia, the most cost-efficient sanction is a uniform, about 20% tariff against all Russian products. Second, if countries are willing to pay at least US0.7 for each US1 drop in Russian welfare, an embargo on Russia's mining and energy products - with tariffs above 50% on other products - is the most cost-efficient policy. Finally, if countries target politically relevant sectors, an embargo against Russia's mining and energy sector is the cost-efficient policy even when there is a small willingness to pay for sanctions.
Keywords: F13; O24; 330; trade sanctions; tariff; tariff competition